Future Clinical Trials in DIPG: Bringing Epigenetics to the Clinic - Morales La Madrid, Andres; Hashizume, Rintaro; Kieran, Mark W. (Frontiers in Oncology, 2015)
In spite of major recent advances in DIPG molecular characterization, this body of knowledge has not yet translated into better treatments.To date,more than 250 clinical trials evaluating radiotherapy along with conventional cytotoxic chemotherapy as well as newer biologic agents,have failed to improve the dismal outcome when compared to palliative radiation alone.The biology of DIPG remained unknown until recently when the neurosurgical expertise along with the recognition by the scientific and clinical community of the importance of tissue sampling at diagnosis;ideally in the context of a clinical trial and by trained neurosurgical teams to maximize patient safety.These pre-treatment tumor samples,and others coming from tissue obtained post-mortem,have yielded new insights into DIPG molecular biology.We now know that DIPG comprises a heterogeneous disease with variable molecular phenotypes, different from adult high grade glioma,other non-pontine pediatric high grade gliomas and even between pontine gliomas.The discovery of histone H3.3 or H3.1 mutations has been an important step forward in understanding tumor formation,maintenance and progression.Pharmacologic reversal of DIPG histone demethylation therefore offers an important potential intervention strategy for the treatment of DIPG.To date,clinical trials of newly diagnosed or progressive DIPG with epigenetic modifiers have been unsuccessful.Whether this failure represents limited activity of the agents used,their CNS penetration,redundant pathways within the tumor,or the possibility that histone mutations are necessary only to initiate DIPGs but not maintain their growth,suggest that a great deal still needs to be elucidated in both the underlying biology of these pathways,and the drugs designed to target them.In this review, we discuss the role of both epigenetic and genetic mutations within DIPG and the development of treatment strategies directed against the unique abnormalities present in this disease.